Self-Healing Polymer Nanocomposites for Composite Structure applications - Gupta, Ranjeetkumar (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium. Nanocomposites offer the possibility of realizing materials with bespoke properties that were un-realizable by the parent pristine materials. Since, nanoscale inclusions firstly engender small mechanical, electrical and optical defects; and secondly the differential property of the large volume of interfacial polymer from the bulk, bestow an opportunity for multi-functionality and attuning desired properties. The proposed research work deals with designing and controlling the interfacial structure-property-function relationships in the nanocomposites. This would give an insight for designing particle-polymer interface in forming hierarchical network of nanoparticles in the polymer matrix, and tackling the exigent issues of agglomeration and uniform dispersion. Upon achieving such to an acceptable limit, there are various possibilities of inducing self-assembling characteristics by engineering the phase interfaces, to design application driven specific properties based nanocomposite materials. This can herald way of delivering enduring structural materials, by the virtue of autonomous self-healing ability, sustaining not just once but multiple or repetitive occasions of damage. The autonomic self-healability triumphs even in the problematic cases where the damage, or its site is hard to identify or even inaccessible. Such engineered self-healing polymer nanocomposites are already finding extensive and promising applications in defence and space expeditions.
Keywords: 'Self-healing'; 'Polymer Nanocomposite'; 'Composite Structures'; 'DSDS17 poster'; 'DSDS17'; 'Nanomaterials'; 'Composite and Hybrid Materials'